KEPEMIMPINAN KOLEKTIF DI PONDOK PESANTREN (STUDI MULTISITUS DI PP. TEBUIRENG JOMBANG, PP. BAHRUL ULUM TAMBAKBERAS JOMBANG DAN PP. MAMBAUL MAâARIF DENANYAR JOMBANG) - Pramitha, Devi (J-PAI: Jurnal Pendidikan Agama Islam, 2018)
Islamic Boarding School is a unique Islamic educational institution, not only because of its existence which has been very long, but also because the culture, methods and networks applied by religious institutions are different from other Islamic educational institutions. The magnitude of the role of boarding school in community empowerment certainly can not be separated from the role of kiai as the owner as well as the leader of pesantren in moving the pesantren community. In leading a boarding school, Kiai has leadership characteristics that vary from one to another, it is also adapted to the characteristics of the boarding school he leads. Today it is true that the leadership of pesantren does not apply single leadership, and pesantren organization has been included in the form of foundation. With this new phenomenon, the pesantren organization leads impersonally, without reducing the kiais role as the supreme leader, then leadership leads to a collective pattern, in accordance with the hierarchy of leadership of a foundation organization.Keyword: Collective Leadership, Islamic Boarding School